(untitled) (CAHIERS MAGELLANES-NS, 2024)
The study examined the various issues and considerations of different stakeholders surrounding the implementation of AI technology in aviation education. It specifically focused on ethical aspects such as safety, privacy, bias, decision-making autonomy, and regulatory compliance. The research utilized semi-structured interviews and thematic analysis to reveal complex perspectives from educators, aviation professionals, regulators, and students. These perspectives shed light on their concerns, expectations, and recommendations. The results revealed a complex landscape in which major stakeholders emphasized the need for extensive testing and validation to ensure the security and reliability of AI systems in critical aviation circumstances. Significant concerns around data privacy and security have arisen, in addition to discussions surrounding the ethical ramifications of AI-powered decision-making in flight operations. Furthermore, the research revealed a unanimous agreement with the necessity of clear and open AI algorithms, strong ethical principles, and ongoing professional training to adequately equip individuals involved in the integration of AI. This research helped to shaping policy, educational practices, and industry standards by thoroughly examining user viewpoints. Its purpose was to promote responsible and useful integration of AI in aviation education.